Justification of Body Mass Index cutoffs for hip and knee joint arthroplasty among California orthopedic surgeons - Sophie V. Orr; Gavin C. Pereira; Blaine A. Christiansen (Journal of Orthopaedic Surgery and Research)
Abstract Background Many orthopedic surgeons choose not to perform joint arthroplasty on patients with a Body Mass Index (BMI) of 35 or above, citing poorer outcomes and increased procedure risk. Identifying and addressing factors surgeons use to determine procedure BMI cutoffs are necessary to increase access to orthopaedic care for this growing patient population. This will help reduce healthcare disparities while also identifying clinical facilities, equipment, training, and procedures that require improvements to accommodate larger individuals. Methods Orthopaedic surgeons were surveyed to identify surgeon-specific BMI cutoffs for hip and knee arthroplasty. The survey was circulated within the California Orthopaedic Association (COA) report during March 2023. Questions aimed to identify BMI cutoffs and justifications such as infection risk, co-morbidities, inadequate equipment, and the American Academy of Orthopaedic Surgeons (AAOS) guidelines. Data on decision making about BMI cutoffs and exceptions were also collected. Results 75% of respondents use BMI cutoffs for hip and knee arthroplasty. 91% of respondents indicated they are either wholly or partially responsible for setting procedure BMI cutoffs. Mean hip and knee arthroplasty BMI cutoffs were 40.5 and 41, respectively. Four categories for BMI cutoff justifications were identified: (1) risk of complications; (2) surgery logistics; (3) concerns about facilities or resources; and (4) surgeon perception. Conclusions BMI-based justifications for denial of care define key addressable areas of improvement that can increase access to care for life-changing orthopaedic surgeries such as THA and TKA. Insight from the queried surgeons will help drive future research areas to address this need.